Comparison of donors julolidine and triphenylamine in TCF-based NLOphoric dyes – a DFT approach. (19th March 2021) - Ghanavatkar, Chaitannya W.; Mishra, Virendra R.; Sekar, Nagaiyan
Abstract : Julolidine or TPA donor and tricyanofuran acceptor systems are selected to assess the 'ground state molecular aspects' and NLO properties of dyes. Six different functionals with five solvents are used to compute vertical excitations and hyperpolarizabilities. The trends in vertical excitations seen in B3LYP functional are comparable with experimental absorption maxima. Intramolecular charge transfer studies correlated with hyperpolarizabilities. The amplitude of sine-shaped potential decreases with an increase in the conjugation chain and solvent polarity. Perturbation potentials have correlation with BLA, quinoid character, hyperpolarizabilities. Increase or decrease in the HOMO–LUMO also depends on the solvent environment. Hyperpolarizabilities, β 0 and γ depend on the solvent polarity and the trends are similar in six different functionals. Standard deviation (SD) is used to benchmark the functional performance. Different DFT descriptors including the relatively new 'hyperhardness' are correlated with calculated NLO parameters. Correlations are quantitatively analysed using regression coefficients. DFT studies show that selected dyes can stand as good NLO material. GRAPHICAL ABSTRACT: